The price of insurance: costs and benefits of worker production in a facultatively social bee. (17th November 2017) - Shell, Wyatt A; Rehan, Sandra M
Abstract : Selection on traits that maximize maternal fitness represents a recurrent mechanism underlying early evolutionary transitions towards social organization. We use genetic and demographic data to perform a cost-benefit analysis comparing alternative reproductive strategies in a bee capable of both subsocial and social nesting. We find that, while alloparental care provides few fitness benefits for worker daughters, social nesting is an advantageous strategy by way of assured fitness returns to social mothers. Abstract: Kin selection theory is foundational in helping to explain the evolution of sociality; however, the degree to which indirect fitness benefits may underlie helping behavior in species of early stage sociality has received relatively little empirical attention. Facultatively social bees, which demonstrate multiple forms of social organization, provide prime systems in which to empirically test hypotheses regarding the evolutionary origins of sociality. The subsocial small carpenter bee, Ceratina calcarata, may establish a social nest by manipulating brood provisions to rear a worker daughter, which then assists in critical late-season alloparental care. Here, we combine nest demographic and behavioral data with genetic relatedness estimates to calculate the relative inclusive fitness of both subsocial and social reproductive strategies in C. calcarata . Social mothers benefit from improved likelihood of brood survivorship and have higher fitness than subsocial mothers. Worker daughters have low indirect fitness on average, and will not produce their own offspring. Among-sibling relatedness is significantly higher in social nests than subsocial nests, though mothers of either reproductive strategy may mate multiply. Though this study corroborates the ultimate role of indirect fitness and assured fitness returns in the evolution of social traits, it also offers additional support for maternal manipulation as the proximate mechanism underlying evolutionary transitions in early stage insect societies.